A New Scoring System to Predict Lymph Node Metastasis and Prognosis After Surgery for Gastric Cancer - Kang, Wen-Zhe; Xiong, Jian-Ping; Li, Yang; Jin, Peng; Xie, Yi-Bin; Xu, Quan; Zhong, Yu-Xin; Tian, Yan-Tao (Frontiers in Oncology, 2022)
Background: Lymph node metastasis is one of the most important factors affecting the prognosis of gastric cancer patients. The purpose of this study is to develop a new scoring system to predict lymph node metastasis in gastric cancer using preoperative tests in various combinations of inflammatory factors and to assess the predictive prognosis value of the new scoring system for the postoperative gastric cancer patients. Method: This study includes 380 gastric cancer patients, 307 in the training set and 73 in the validation set. We obtain three inflammatory markers, CRA (C-reactive protein/albumin), SIRI (systemic inflammatory response index), and PLR (platelets/lymphocytes), by calculating and comparing the results of preoperative laboratory tests. By using these three indicators, a new scoring system is developed to predict lymph node metastases, assess patient’s prognoses, and compare clinicopathological characteristics in different patients subgroups. Nomogram is constructed to show and assess the predictive efficacy of every index for lymph node metastasis and survival. Results: In the new scoring system, higher scores are associated with more advanced pathological stage (p< 0.001), Perineural invasion (p< 0.001), and Vascular invasion (p=0.001). Univariate and multivariable cox regression analysis show that Perineural invasion, Vascular invasion, Smoking history, and high scores on the new scoring system are significant risk factors for OS and RFS. High scoring subgroups as an independent prognostic factor could predict overall survival (OS) and relapse-free survival (RFS). High scores on the new scoring system are significantly associated with the degree of lymph node metastasis (p< 0.001). CAR and PLR play very important roles in predicting lymph node metastasis in gastric cancer. CAR is a vital major marker in the prediction of patient survival. Conclusions: The new scoring system can effectively predict the patients’ lymph node metastasis with gastric cancer and can independently predict the prognosis of patients.